Analisis Aspek - Aspek Pembelajaran Pada Sistem Persekolahan Terhadap Hasil Belajar Siswa - Riswanto, Ari (2020)
This study examines the main issues related to whether there is influence between learning dimensions of student learning outcomes seen from the school system used in the school? Data were collected through observation, interview, documentation study, and literature study. The method used in this research use descriptive and verifikatif research type. The research instrument is a questionnaire that has been tested the validity and reliability as well as distributed with survey techniques. Data analysis was done by several stages: data collection, data organizing, descriptive anaisis and linear and multiple regression analysis. The result of this research is 1). The dimensions of learning in high school education in Sukabumi City are mostly quite good, although there are still some shortcomings in the learning model learning dimension; 2). Learning Outcomes of high school students in Sukabumi City tend to decrease in terms of categories ranging from points UTS, UAS and UN; 3). Learning models have an influence on student learning outcomes; 4). The learning curriculum has an influence on student learning outcomes; 5). Learning facilities have an influence on learning outcomes; 6). The overall learning dimensions have a lethal effect on student learning outcomes; 7). The highest effect of learning dimensions on student learning outcomes occurs in the learning system boarding school, then fullday school and last regular school. Suggestions in this study is more maximized preparation and implementation also completeness of learning dimension to improve student learning outcomes.